“KAMU ADALAH BIDADARIKU”: KAJIAN METAFORA KONSEPTUAL TERHADAP WACANA RAYUAN DI INDONESIA - Anandya Asprillia (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2022)
Flattery is an expression uttered to get someone’s attention or showing affection in order to initiate romantic relation Flattery is generally known to be expressed in form of metaphor. On the other hand, metaphor can also reflect the thought and culture of a society. Thus, this research aims to identify and explain the conceptualization that involves the concept of KAMU (YOU) into the target domain in Indonesian flattery. This research will also give a representation of how the concept of KAMU is used in Indonesia. This is qualitative research with data taken from Indonesian online sources. The data are analyzed using Conceptual Metaphor that explains the target domain from the source domain KAMU and how it relates to the culture in Indonesian society. The analysis showed that KAMU in the Indonesia flatteries have several target domains, namely TULANG RUSUK (RIB), MALAIKAT (ANGEL), BIDADARI (NYMPH), and PEMBAWA SURGA (HEAVEN’S BEARER). The target domain TULANG RUSUK and PEMBAWA SURGA indicate Indonesian conceptualization where the flattery speaker wants the interlocutor becomes a lifetime partner in a marriage bond. Those target domains are rooted in Islamic hadith, which is a religion for most Indonesian. While ANGEL and NYMPH target domains indicate that the speaker flatters the interlocutor as a good-looking and behaving person. This finding of this research generally reflects how religion and culture in Indonesia can affect its language.